Effects of culture density and live prey on growth and survival of juvenile cuttlefish, Sepia officinalis - Domingues, P. (2018)
The European cuttlefish, Sepia offıcinalis Linnaeus 1758, has a number of characteristics, such as a fast growth rate and benthic life style, which make this one of the most promising species for large-scale culture (Domingues 1999). One of the key factors in large-scale aquaculture is to optimise growth while minimizing the culture space required (Forsythe et al. 2002). Until now, only Nabhitabhata (1999) and Forsythe et al. (1994), Koueta and Boucaud-Camou (1999) indicated stocking densities for cultured cuttlefish populations. Laboratory-cultured cuttlefish have been studied in several aspects of their behaviour. Nevertheless, effects of tank size and animal density on growth, condition and reproduction are not known (Boal et al. 1999). Crowding can have a major effect on growth and behaviour in many species, and in aquaculture this factor can be very important (Sumpter 1993).